Rethinking the Paleogene Tectonostratigraphy and Petroleum Systems of Indonesia: Moving Beyond Simplistic Basin Models - Ian Longley (Ikatan Ahli Geologi Indonesia, 2026)
A pervasive paradigm in Southeast Asian geosciences posits a uniform, synchronous tripartite sequence for Paleogene basin evolution: regional rifting, thermal sag, and middle-to-late Miocene structural inversion. However, critical evaluation of hard chronostratigraphic and structural data reveals this rigid model is overly simplistic and frequently inaccurate. Instead, the Paleogene basins of Indonesia exhibit highly localized, diachronous, and episodic tectonic events that cannot be explained by regional generalizations like the rigid